Postoperative C-Reactive Protein Predicts Postoperative Delirium in Colorectal Cancer Following Surgery - Sun Y; Peng HP; Wu TT (Clinical Interventions in Aging, 2023)
Yan Sun, Hui-Ping Peng, Ting-Ting Wu Department of Anesthesiology, First Affiliated Hospital of Soochow University, Suzhou, Jiangsu, People’s Republic of ChinaCorrespondence: Ting-Ting Wu; Hui-Ping Peng, Email wttsy2022@163.com; peng871231@163.comBackground: Postoperative delirium (POD) is a common complication in operative patients. Neuroinflammation has been reported to be a potential mechanism associated with the development of POD. Identifying available inflammatory markers such as C-reactive protein (CRP) would aid clinicians in early detection of POD. Previous studies have demonstrated that CRP may be a promising predictive marker for POD. Thus, this study aimed to explore the association between CRP and POD among those elderly colorectal cancer (CRC) patients.Methods: 643 patients with CRC were included in this study. CRP levels were measured before operation and on postoperative day 1. The univariate and multivariate regression analyses were used to identify risk factors for POD.Results: Of 643 patients with CRC, 112 cases (17.4%) had POD. CRC patients with POD showed older age, higher CRP level on postoperative day 1, and higher percentage of smoking, diabetes mellitus, and chronic obstructive pulmonary disease (COPD) than CRC patients without POD. Preoperative CRP level was not associated with the POD. Univariate and multivariate regression analyses showed that older age (> 70 years), diabetes mellitus, COPD, and higher CRP level on postoperative day 1 (> 48 mg/L) were risk factors for POD in CRC patients.Conclusion: Postoperative CRP level is an independent indicator for POD among CRC patients, suggesting the predictive role of postoperative CRP levels for POD in elderly CRC patients undergoing surgery.Keywords: postoperative delirium, C-reactive protein, colorectal cancer